2017
DOI: 10.1016/j.drugalcdep.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

The association between regular marijuana use and adult mental health outcomes

Abstract: Objective The present study is a prospective examination of the relationship between regular marijuana use from adolescence through young adulthood and mental health outcomes at age 33. Methods Data came from a gender-balanced, ethnically diverse longitudinal panel of 808 participants from Seattle, Washington. Outcomes included symptom counts for six mental health disorders. Regular marijuana use was tracked during adolescence and young adulthood. Regression analyses controlled for demographics and early env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 56 publications
3
38
0
Order By: Relevance
“…Both clinical and epidemiological studies have consistently shown that co-use of alcohol and cannabis leads to more physiological, cognitive and behavioral impairment than the use of either substance alone (Chait and Perry, 1994; Downey et al, 2013; Ramaekers et al, 2001; Ronen et al, 2008; Subbaraman, 2016; Subbaraman and Kerr, 2015), which supports the findings that the heaviest cannabis users had more physical problems and injuries attributable to alcohol. However, cannabis use specifically has been linked to depression and/or anxiety, diminished lifetime achievement, and abnormal brain development as well (Guttmannova et al, 2017), which suggests that cannabis use would exacerbate alcoholrelated inter- and intrapersonal problems, as well as impulse control and social responsibility. Although we did see that higher frequencies of cannabis use were related to problems with impulse control and social responsibility at both end of treatment and one-year post-treatment in bivariate tests, these results were not robust to multivariable model specifications in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical and epidemiological studies have consistently shown that co-use of alcohol and cannabis leads to more physiological, cognitive and behavioral impairment than the use of either substance alone (Chait and Perry, 1994; Downey et al, 2013; Ramaekers et al, 2001; Ronen et al, 2008; Subbaraman, 2016; Subbaraman and Kerr, 2015), which supports the findings that the heaviest cannabis users had more physical problems and injuries attributable to alcohol. However, cannabis use specifically has been linked to depression and/or anxiety, diminished lifetime achievement, and abnormal brain development as well (Guttmannova et al, 2017), which suggests that cannabis use would exacerbate alcoholrelated inter- and intrapersonal problems, as well as impulse control and social responsibility. Although we did see that higher frequencies of cannabis use were related to problems with impulse control and social responsibility at both end of treatment and one-year post-treatment in bivariate tests, these results were not robust to multivariable model specifications in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, regarding generalized anxiety disorder (GAD), research ranges from a two-fold increased risk of anxiety symptoms with cannabis use to no significant association between the two factors [37,144]. One study supports the relationship between cannabis use and GAD, but not between cannabis use and SAD, further complicating the results [66], while others describe persistent reports of heightened anxiety symptoms in cannabis users compared to non-users [42]. Some studies have investigated the effects of cannabis use in early childhood and adolescent stages, demonstrating an increased risk of developing anxiety symptoms and anxiety disorder, which was strengthened with earlier onset of cannabis use [25,36,69].…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…[7,19] There is equivocal evidence suggesting either positive or lack of statistically significant associations between cannabis use and anxiety disorder or anxiety symptoms. [27,34,37,50,66,69,130,144] Randomized, controlled trials and longitudinal, prospective studies are needed to associate specific preparations of cannabis with anxiety outcomes and risk for anxiety development.…”
Section: Gadmentioning
confidence: 99%
“…In addition to the potential physical health consequences, considerable evidence shows an increased risk of mental health disorders associated with cannabis use [60]. However, there is insufficient evidence to fully describe these associations.…”
Section: Cognitive and Mental Health Concernsmentioning
confidence: 99%
“…Here we will discuss the evidence for the association of cannabis with psychosis, schizophrenia, anxiety and depression. In addition to these disorders, patients diagnosed with cannabis use disorder (dependence or addiction) have a higher risk of developing other substance-use disorders, eating disorders, conduct disorders and personality disorders [3,60].…”
Section: Impact Of Chronic Consumptionmentioning
confidence: 99%